Evaluation of Gentamicin Release of PMMA Cements Using Different Methods: HPLC, Elution and Inhibition Zone Testing - Clemens Kittinger; Johannes Stadler; Klaus Dieter Kühn (MDPI AG, 2024)
(1) Background: There is an ongoing discussion on the elution efficacy of antibiotic-impregnated cements. Our experiments were intended to clarify if there are differences in the antibiotic elution of HPLC compared with inhibition zone testing using eluates or PMMA discs. (2) Materials and Methods: Two cement brands with different concentrations of the active ingredient were tested in antimicrobial Kirby-Bauer (disc diffusion) assays. Cement platelets were directly applied on the agar plates and their zone of inhibition was measured. In parallel, the platelets were incubated in phosphate buffered saline (PBS) and at distinct points of time transferred into new buffer. At these time points, 50 µL of the bone cement eluates was used for zone of inhibition testing. Standard gentamicin sulfate solutions served as a control in the same test setup. To verify the microbiological investigations, the antibiotic content of the eluates was also measured via high-performance liquid chromatography (HPLC). (3) Results: The experiments with cement eluates showed better differentiable results than the direct application of the cement discs. The results were also comparable to investigations with HPLC and gentamicin sulfate standard solutions. (4) Conclusions: The results of elution rates are influenced by the test system and the period of observation chosen. The microbial test systems reflect the results of HPLC to the same degree and give evidence of the efficacy of the antibiotics. The HPLC tests on eluates were more suitable in representing differences in release characteristics.